Ending ageism : or, how not to shoot old people - Gullette, Margaret Morganroth (Global perspectives on aging, 2017)
In Ending Ageism, or How Not to Shoot Old People, award-winning writer and cultural critic Margaret Morganroth Gullette raises urgent legal, economic, educational, esthetic, and ethical issues to show why anti-ageism should be the next social movement of our time.